Thromboprophylaxis using combined intermittent pneumatic compression and pharmacologic prophylaxis versus pharmacologic prophylaxis alone in critically ill patients: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Arabi, Yaseen M; Alsolamy, Sami; Al-Dawood, Abdulaziz; Al-Omari, Awad; Al-Hameed, Fahad; Burns, Karen; Almaani, Mohammed; Lababidi, Hani; Al Bshabshe, Ali; Mehta, Sangeeta; Al-Aithan, Abdulsalam; Mandourah, Yasser; et al.
Abstract Background Venous thromboembolism (VTE) remains a common problem in critically ill patients. Pharmacologic prophylaxis is currently the standard of care based on high-level evidence from randomized controlled trials. However, limited evidence exists regarding the effectiveness of intermittent pneumatic compression (IPC) devices. The Pneumatic compREssion for preventing VENous Thromboembolism (PREVENT trial) aims to determine whether the adjunct use of IPC with pharmacologic prophylaxis compared to pharmacologic prophylaxis alone in critically ill patients reduces the risk of VTE. Methods/Design The PREVENT trial is a multicenter randomized controlled trial, which will recruit 2000 critically ill patients from over 20 hospitals in three countries. The primary outcome is the incidence of proximal lower extremity deep vein thrombosis (DVT) within 28 days after randomization. Radiologists interpreting the scans are blinded to intervention allocation, whereas the patients and caregivers are unblinded. The trial has 80 % power to detect a 3 % absolute risk reduction in proximal DVT from 7 to 4 %. Discussion The first patient was enrolled in July 2014. As of May 2015, a total of 650 patients have been enrolled from 13 centers in Saudi Arabia, Canada and Australia. The first interim analysis is anticipated in July 2016. We expect to complete recruitment by 2018. Trial registration Clinicaltrials.gov:NCT02040103 (registered on 3 November 2013). Current controlled trials:ISRCTN44653506 (registered on 30 October 2013).